2004
DOI: 10.1210/jc.2003-031252
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Polycystic Ovary Syndrome with Genomic Variants Related to Insulin Resistance, Type 2 Diabetes Mellitus, and Obesity

Abstract: We have evaluated the possible association of polycystic ovary syndrome (PCOS) with 15 genomic variants previously described to influence insulin resistance, obesity, and/or type 2 diabetes mellitus. Seventy-two PCOS patients and 42 healthy controls were genotyped for 15 variants in the genes encoding for paraoxonase (three variants), plasma cell differentiation antigen glycoprotein, human sorbin and SH3 domain containing 1, plasminogen activator inhibitor-1, peroxisome proliferator-activated receptor-gamma2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 70 publications
11
102
1
4
Order By: Relevance
“…Problematic to genetic association studies are differences in ethnic background and small sample sizes, both of which can lead to spurious results. Whereas most studies (9)(10)(11)(12)14,15), present study included, reported no association between Pro12Ala genotype and PCOS diagnosis, a few reported that the Pro12Ala G allele was significantly less frequent in PCOS versus control women (13,16). Additionally, some studies reported significant increases in insulin sensitivity (decreased HOMA-IR) and decreases in fasting insulin and glucose levels (8-10) and lower hirsutism score (9) in PCOS women with the Pro12Ala G allele; whereas others (7,11,14), including this study, reported no association with fasting glucose and insulin or changes in HOMA-IR in those with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problematic to genetic association studies are differences in ethnic background and small sample sizes, both of which can lead to spurious results. Whereas most studies (9)(10)(11)(12)14,15), present study included, reported no association between Pro12Ala genotype and PCOS diagnosis, a few reported that the Pro12Ala G allele was significantly less frequent in PCOS versus control women (13,16). Additionally, some studies reported significant increases in insulin sensitivity (decreased HOMA-IR) and decreases in fasting insulin and glucose levels (8-10) and lower hirsutism score (9) in PCOS women with the Pro12Ala G allele; whereas others (7,11,14), including this study, reported no association with fasting glucose and insulin or changes in HOMA-IR in those with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a polymorphism in exon 2 of the PPARγ2 isoform, resulting in a Pro12Ala substitution, influences the risk of type 2 diabetes with the rarer Ala allele associated with a lower incidence of diabetes (6). Several small studies have looked at the effects of the Pro12Ala and a silent exon 6 polymorphism (His447His) in association with PCOS, though they have produced conflicting results (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). To better understand the role of these polymorphisms in PCOS, we examined the Pro12Ala and silent exon 6 polymorphism in a cohort of 285 women with PCOS and 187 controls, the largest sample size of all published reports of PPARG in PCOS to date.…”
mentioning
confidence: 99%
“…San Millan et al (27) reported that homozygosity for T alleles (decreased PON1 gene expression) of the PON1 K108C/T polymorphism presented with increased hirsutism scores and serum testosterone concentrations when compared with carriers of K108C alleles. Our findings that in patients with normal body weight (BMI !25), the carriers with 192R alleles have significantly higher TT levels when compared with the patients with QQ genotype, prompt that 192R allele may also contribute to HA in these patients.…”
Section: Control Group Pcos Groupmentioning
confidence: 99%
“…However, up to now, only a few reports regarding the possible connection between the PON1 and PCOS are available. Dursun et al (26) reported that serum PON activity was decreased in patients with PCOS compared with control women, and San Millan et al (27) reported that homozygosity for T alleles of the K108C/T, but not 192Q/R and 55M/L, polymorphism in PON1 was more frequent in women with PCOS (nZ72) compared with nonhyperandrogenic control women (nZ42) in Spain. In contrast with the previous reports, our recent study showed that the K108C/T polymorphism in the PON1 gene was not associated with the risk of PCOS in Chinese women (28).…”
Section: Introductionmentioning
confidence: 99%
“…35 And in the study of Dursun et al, the serum paraoxanase level of PCOS patients has been found to be lower than that of control group.…”
mentioning
confidence: 94%